2017
DOI: 10.1016/j.rboe.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

One-year mortality of elderly patients with hip fracture surgically treated at a hospital in Southern Brazil

Abstract: ObjectiveTo analyze the mortality rate at one-year follow-up of patients with hip fracture who underwent surgery at the university hospital of this institution.MethodThe authors reviewed 213 medical records of hospitalized patients aged 65 years or older, following to the order they were admitted to the orthopedics and traumatology service from January 2012 to August 2013.ResultsOne-year mortality rate was 23.6%. Mortality was higher among women, with a 3:1 ratio. Anemia (p = 0.000) and dementia (p = 0.041) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
2
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 28 publications
4
20
2
11
Order By: Relevance
“…Hip fracture in the elderly is an important problem that can lead to death. Many studies reported the mortality rates of hip surgery after 1 year ranged from 12.7 to 29.2% [5][6][7][8]. In our study, the total mortality rate 1 year after injury was 16.6%, similar to those reported previously.…”
Section: Discussionsupporting
confidence: 90%
“…Hip fracture in the elderly is an important problem that can lead to death. Many studies reported the mortality rates of hip surgery after 1 year ranged from 12.7 to 29.2% [5][6][7][8]. In our study, the total mortality rate 1 year after injury was 16.6%, similar to those reported previously.…”
Section: Discussionsupporting
confidence: 90%
“…The mortality rate reported in the literature ranges from 23.6% to 35.0%. 14 , 15 The mortality rate did not change from 2006 13 to the present study despite the fact that the number of fractures increased. In 2008, Haleem et al.…”
Section: Discussioncontrasting
confidence: 51%
“…As such, we believe that the demographics of Forster et al 12 may justify the higher mortality rates in their study, since our investigation revealed that older age and longer hospitalization periods increase the mortality rate. 13 14 15 16 17 18 19 On the other hand, compared to our study, Garcia et al 20 obtained a lower mortality rate at 6 months and at 1 year of follow-up (14% and 30%, respectively), as did Guerra et al, 13 with a 1-year mortality rate of 23.6%. Wood et al 21 and Parker et al 22 observed mortality rates of ∼ 14% at the 1-year follow-up.…”
Section: Discussionsupporting
confidence: 48%